Linguistic Taxonomy of Language Errors in Scientific Writing by Twelfth-Grade Students of MA Nusantara - Tsabit AJ, Ibnu; Septiani, Dwi (LITERATUR : Jurnal Bahasa dan Sastra, 2025)
This study aims to describe the form of language errors at the level of phonology, morphology and syntax in the writings of MA Nusantara class XII students. The data source of this research is MA Nusantara students' writing in 2023. The method used is descriptive qualitative. The data were obtained using the listening method and note-taking technique. Data analysis uses a flow chart analysis model. The stages of this model analysis are data reduction, data presentation, and conclusion drawing. The results of the study found language errors at the phonological level as much as 667 data, language errors at the morphological level as much as 17 data, and language errors at the syntactic level as much as 97 data.  Language errors made by students need to be evaluated as soon as possible, because they illustrate language learning that has not been achieved. The higher the quantity of errors, the greater the language learning objectives that have not been achieved. In addition, the quantity of errors can be the teacher's benchmark for students' language competence.